Learning uncomfortably - Sadowska, Noemi; Laffy, Dominic (Border Crossing, 2011)
This paper outlines a research process entwined with delivery of a final year elective module “Managing Strategic Design”. This module challenges a mixture of business and design management final year undergraduate students to devel-op truly innovative business opportunities. The research has been based on six roundtable discussions with a variety of participants from design and business communities, as well as classroom observation and reflections from students on the aforementioned elective module. The process of creating these innovative opportunities is at times deeply uncomfortable but it is at these points that stu-dents’ learning can be most productive. The iterative process of research and teaching have led us, the authors, to reflect on the value and positioning of de-sign and strategic thinking in business education: the methodology behind our particular curriculum delivery drawing on cross disciplinary teaching and learn-ing; and the ability of students to learn from practice by experiencing ‘zones of discomfort’ and ‘what if’ scenarios. These reflections have altered the focus of the elective module, from provision of tools students need to know to under-standing the learning journey and facilitating the acquisition of decision-making confidence in response to a complex challenge.